2016
DOI: 10.4103/2249-4863.192336
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum versus bronchial washings in the diagnosis of sputum negative pulmonary tuberculosis

Abstract: Introduction:Tuberculosis (TB) is one of the most important public health problems worldwide. Detecting patients with active pulmonary TB (PT) is an important component of TB control programs. However, at times in patients even with a compatible clinical picture, sputum smears do not reveal acid-fast bacilli (AFB) and smear-negative PT remains a common problem. This study compares the results of induced sputum (IS) and bronchial washings (BWs) in detecting sputum negative PT.Materials and Methods:A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These small airways may also communicate with cavities in the lung parenchyma where bacilli are concentrated [39]. Further evidence comes from the consistently high sensitivity of broncho-alveolar lavage in TB, even in cases with negative sputum culture [40,41]. This suggests that viable Mtb bacilli are to be found in the lower airways.…”
Section: Resultsmentioning
confidence: 99%
“…These small airways may also communicate with cavities in the lung parenchyma where bacilli are concentrated [39]. Further evidence comes from the consistently high sensitivity of broncho-alveolar lavage in TB, even in cases with negative sputum culture [40,41]. This suggests that viable Mtb bacilli are to be found in the lower airways.…”
Section: Resultsmentioning
confidence: 99%
“…The various studies in this regard has reported the diagnostic yield varying from 35 to 95% [17]. There have been few studies reported in which the results of sputum induction and FOB related procedures have been compared and all have reported FOB superior to sputum induction [18][19][20]. But very few studies in this regard have been reported under RNTCP settings.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, patients with high clinical suspicion of PTB who were unable to generate adequate sputum or have smear-negative sputum may have a high probability of smear positivity on bronchoalveolar lavage (BAL) [ 25 ]. Another study found the added value of bronchoscopy over induced sputum to be 15% in identifying smear-positive TB in patients with previous smear-negative sputum [ 26 ]. In our study, it influenced management in only one patient.…”
Section: Discussionmentioning
confidence: 99%